Inclusion Characteristics of the Fracture-Cave Calcite of Ordovician Yingshan Formation and Its Indication to the Formation of Paleokarst Reservoir in the Northern Slope of Tarim Basin Center Area, China - Dan, Yong; Ba, Junjie; Liang, Bin; Zhang, Qingyu; Li, Jingrui; Nie, Guoquan (Frontiers in Earth Science, 2022)
A karst fracture-cavity was developed in the Ordovician Yingshan Formation in the northern slope of Tarim Basin center area (Tazhong area); however, the area experienced multistage karst and diagenesis in the later period, and the reservoir was heavily reformed, characterized by a complex distribution. Based on testing of the inclusions in the karst fractures and fracture-cave calcite, this paper summarizes the physical and chemical characteristics of the inclusions in the northern slope of Tazhong area. The major inclusions were liquid and gas–liquid phases, while the minor ones were hydrocarbon phases. Based on the salinity–homogenization temperature diagram, the gas–liquid inclusions could be divided into seven types: low-temperature low-salinity inclusions (the lowest salinity was 0.88%, which is lower than that of present sea water; the lowest temperature of the inclusions was 49 °C), low-temperature high-salinity inclusions, medium-temperature low-salinity inclusions, medium-temperature medium-salinity inclusions, medium-temperature high-salinity inclusions, high-temperature medium-salinity inclusions, and high-temperature high-salinity inclusions. The development of inclusions was characterized by high temperature and high salinity or low temperature and low salinity. In addition, the low-temperature and low-salinity inclusions near the unconformity surface were well developed. The high-temperature and higher-salinity inclusions far from the unconformity surface were also well developed. A burial history analysis showed three stages of karstification or filling in the area: exposed karstification in the Middle Caledonian, shallow burial filling in the Middle Hercynian, and burial filling in the Late Hercynian. By determining the inclusions in calcite associated with mud in the karst caves and combined with previous studies, the Middle The Caledonian was found to be the period associated with the eogenetic karstification of meteoric water and seawater. This is the key factor in the formation of karst reservoirs in the Tazhong area. The large-scale calcite growth in the Middle Hercynian and Late Hercynian burial periods led to further filling of the early karst reservoir, reduced the reservoir space, and enhanced the reservoir heterogeneity.